Elementy kreatywnego wykonania w krajowej reklamie prasowej: wyniki badania - Woźniczka, Jarosław (Elements of Creative Execution Observed in 250 Print Advertisements Placed in Polish Magazines and Newspapers, 2008)
The article presents the results of the descriptive analysis of typical elements of creative execution observed in 250 print advertisements placed in 12 magazines and newspapers on the Polish market. It is a part of a bigger research project dedicated to the creative strategy in print advertising. During the analysis certain types of advertising headlines, slogans, body copy, illustrations and layout were identified, defined and characterized. Then the frequency of appearance of these types in the observed advertisements was calculated and the extent of their diversity and their communication usefulness were evaluated.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 33, s. 121-137